Childhood Obesity: Does it Have Any Effect on Young Arteries? - Jakab, Andrea Emese; Hidvégi, Erzsébet Valéria; Illyés, Miklós; Cziráki, Attila; Kalmár, Tibor; Maróti, Zoltán; Bereczki, Csaba (Frontiers in Pediatrics, 2020)
Prevalence of overweight (OW) and obesity (O) in children and adolescents has been increased in the past three decades. Increased arterial stiffness measuring by aortic pulse wave velocity (PWVao) might be detected in OW/O children and adolescents. The aim of our study was to compare the arterial function parameters (AFPs), such as PWVao; aortic augmentation index (Aixao); aortic systolic blood pressure (SBPao) and brachial systolic blood pressure (SBPbrach) measured simultaneously in O/OW patients and healthy subjects. In our study 6,816 subjects (3,668 boys) aged 3–18 years were recruited and categorised by their body mass index (BMI) into normal weight (N), OW and O groups regarding their age and sex. AFPs were measured by a non-invasive, occlusive-oscillometric device. 19.9% (n=1,356) of the population were OW/O, 911 (516 boys) were OW and 445 (272 boys) were O. After accounting for the effect of covariates, PWVao did not differ significantly between N (5.9±0.8 m/s) and OW patients (5.9±0.8 m/s); and N (6.0±0.7 m/s) and O patients (6.0±0.8 m/s). Aixao was significantly lower in OW (9.3±7.4% vs 7.6±7.0%, p<0.00001) and in O patients (9.7±8.1% vs 6.6±7.2%, p<0.00001) compared to controls. No significant difference was found regarding SBPao values between controls and OW and O groups (N=110.7±12.4 mmHg vs OW=110.3±11.9 mmHg; N=115.6±14.0 mmHg vs O=114.3±12.8 mmHg). According to our results, we may conclude that the unchanged PWVao in O/OW subjects might be due to the compensatory decrease in Aixao, referring to enhanced vasodilatory status in the studied population.